2003
DOI: 10.1093/oxfordjournals.rpd.a006333
|View full text |Cite
|
Sign up to set email alerts
|

Dose rate effect on micronucleis induction in cytokinesis blocked human peripheral blood lymphocytes

Abstract: The effect of dose rate on the induction of micronuclei (MN) in human peripheral blood lymphocytes was investigated over a range of dose rates from 0.125 Gy h(-1) to 178.2 Gy h(-1). The response of MN induction was fitted with a linear quadratic model and the alpha and beta coefficients were estimated. It was found that beta values decrease with decreasing dose rate as in the case of chromosomal aberration. At the dose rate of 0.125 Gy h(-1), pure linear response of MN induction was observed. An attempt was ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Radiation-induced chromosomal aberrations observed as MNi in peripheral blood lymphocytes are largely the result of unrepaired or misrepaired DSBs by the non-homologous end-joining pathway (36, 38). The dose-response relationship for micronuclei frequencies in human (39, 40) and mouse (41) peripheral blood lymphocytes (PBLs) in vitro after acute doses of ionizing radiation can be fitted with the linear-quadratic model. Studies aimed to investigate dose-rate effects for radiation-induced micronucleus formation in human lymphocytes reported that MNi yields decreased with decreasing dose rates (39, 42, 43).…”
Section: Introductionmentioning
confidence: 99%
“…Radiation-induced chromosomal aberrations observed as MNi in peripheral blood lymphocytes are largely the result of unrepaired or misrepaired DSBs by the non-homologous end-joining pathway (36, 38). The dose-response relationship for micronuclei frequencies in human (39, 40) and mouse (41) peripheral blood lymphocytes (PBLs) in vitro after acute doses of ionizing radiation can be fitted with the linear-quadratic model. Studies aimed to investigate dose-rate effects for radiation-induced micronucleus formation in human lymphocytes reported that MNi yields decreased with decreasing dose rates (39, 42, 43).…”
Section: Introductionmentioning
confidence: 99%
“…Micronucleus frequency in lymphocytes exposed to low LET radiation such X-rays, gamma rays, and electron beams increases linearly-quadratically with the absorbed dose, indicating a contribution of both single and multi-track lesions (16,25,26). Therefore, MN frequency is clearly infl uenced by dose rates.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown remarkable variation in biological damages with pulse frequency. Bellucci (31) showed that 20 pulses per second was the most lethal dose rate for cells in the pulse range of four to 24 pulses per second, while Hood and Norris (32) found no variations in lethality of normal and malignant human cells exposed to pulsed X-ray in the wide range of 1x10 5 to 3x10 5 pulses per minute. A signifi cant depletion in oxygen concentration was demonstrated when doses were given in a single pulse.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations